Techno- and Ethnocentrism in Organizational Studies: Comment and Speculation Prompted by Ronen and Shenkar - Blunt, Peter (Academy of Management Review, 1986)
The article presents a response to the 1985 article “Clustering Countries on Attitudinal Dimensions,” by S. Ronen and O. Shenkar. The author states that the article presents a misleading claim that many areas of Africa have not been studied, and provides a list of studies that prove that research has been done in Africa. The author discusses further general concerns: technocentrism and ethnocentrism in organizational studies. The author gives examples of why he believes countries are only interested in organizational research originating from their own researchers.